Behavior of Vibrio spp. in Table Olives - Posada-Izquierdo, Guiomar Denisse; Valero, Antonio; Arroyo-López, Francisco Noé; González-Serrano, Miriam; Ramos-Benítez, Alfonso M.; Benítez-Cabello, Antonio; Rodríguez-Gómez, Francisco; Jimenez-Diaz, Rufino; García-Gimeno, Rosa M. (Frontiers in Microbiology, 2021)
Presence of exogenous Vibrio species in table olive fermentations have been confirmed by molecular biology techniques in recent studies. Although there has not been any foodborne toxiinfection caused by Vibrio due to table olives consumption, their role as well as the environmental conditions allowing survival in table olives has not been elucidated so far. The purpose of this work was to model the behavior of an exogenous Vibrio cocktail in diverse table olive environments. First, a challenge testing was done in lye treated olives inoculated at the beginning of fermentation with the Vibrio cocktail for 22 days. Afterwards, an in vitro study has been performed where the microbial behavior of a Vibrio cocktail was evaluated in laboratory medium and in olive brines using predictive models at different NaCl concentrations (2-12%) and pH levels (4.0-9.0). Results showed Vibrio species have not been detected in olive brines during fermentation in different pH. However, the that optimal growth conditions in laboratory medium for Vibrio cocktail, according to what was observed, we established that are those of pH 9 and 2% salt, with a latency period of 0 hours and a maximum population density of 1,242DO, the other hand, the maximum growth rate was observed at pH 8 and 2% salt with 0.059DO. The statistical analysis demonstrated that the effect of salt concentration was higher than pH for the kinetic growth parameters (µmax, lag phase, yEnd). On the other hand, we confirmed that no growth of the Vibrio cocktail was noticed during lye treated olive fermentations. Thus, it was concluded that presence of olive compounds (unknow) did not allow the development of exogenous Vibrio strains, and consequently, native Vibrio spp. related with olive environments may be better adapted to the stressing conditions which governs olive processing should be proposed for future studies.